Der Fall Roms und seine Wiederauferstehungen in Antike und Mittelalter - Pollmann, Karla; Harich-Schwarzbauer, Henriette (Millennium-Studien / Millennium Studies, 2013)
This collection of essays analyzes the construction of the "fall" of Rome from a range of perspectives native to different disciplines. Subjects addressed include comparable discourses dating from the earlier history of Rome, the perception of this historical moment by writers living at the time it occurred, and its reception in Byzantium and Western Europe during the Middle Ages.